Gut Microbiota in Type 2 Diabetes Mellitus: Mechanistic Pathways, Microbiota-Targeted Strategies, and Clinical Implications — A Narrative Review - Szewczyk, Konrad; Janasik, Laura; Kociucka, Patrycja; Modelska, Julia; Sadowski, Krzysztof; Jeleń, Anita; Podolska, Anna; Siwicka, Katarzyna; Paluchowicz, Karolina (Journal of Education, Health and Sport, 2026)
Type 2 diabetes mellitus (T2DM) is a complex metabolic disorder increasingly associated with changes in the composition and function of the gut microbiota. A growing body of evidence suggests that microbial metabolites, immune modulation, and intestinal barrier integrity play a key role in regulating insulin sensitivity and chronic low-grade inflammation. This literature review synthesizes current mechanistic, clinical, and translational evidence on the gut microbiota–metabolic axis in T2DM, with a particular focus on short-chain fatty acids, bile acid signaling, branched-chain amino acids, tryptophan metabolites, and novel microbiota-derived compounds. Key pathways include metabolic endotoxemia, incretin regulation, immune modulation, and the influence of the microbiota on pharmacotherapy and lifestyle factors such as diet and physical activity. Clinical studies indicate that changes in the microbiota correlate with glycemic control, markers of inflammation, and disease progression, while microbiota-targeted strategies—including dietary interventions, prebiotics, probiotics, and selected antidiabetic drugs—may contribute to improved metabolic outcomes. However, study design heterogeneity, population differences, and methodological limitations currently hinder causal interpretation. Future studies combining multiomic approaches and personalized interventions may help elucidate the therapeutic potential of microbiota modulation in T2DM. Overall, the gut microbiota appears to be a dynamic regulator of immunometabolic homeostasis and a promising target for future precision-based strategies in the treatment of metabolic diseases.